Energy dissipation capacity of cementitious nanocomposite reinforced by hybrid carbon nanotubes. (14th March 2022) - Jazaei, Robabeh; Karakouzian, Moses; O'Toole, Brendan; Moon, Jaeyun; Gharehdaghi, Samad
Graphical abstract: Highlights: Energy absorption and failure mechanism were improved by using hybrid carbon nanotubes. Synthetized hybrid and single-walled carbon nanotubes decreased workability which was improved by water-to-cement ratio correction. Both carbon nanotubes dispersion and mixing procedure effects on the failure mechanism. The effect of sonication time and orbital vibration on the cement-based composite samples were studied. The experiment was designed to perform and examine the low-velocity impact test. Abstract: Nanomaterials have a significant effect on the construction industry in terms of modifying concrete properties. However, accelerated microcracks due to brittle nature of cement paste cause low energy absorption in cement-based composites. Carbon nanotubes (CNTs) are promising materials to address this problem if not all. The main objective of this experimental investigation is to assess the effect of reinforcing cement-based composites with the low dosage of functionalized (COOH group) hybrid carbon nanotubes (single-walled and multi-walled carbon nanotubes). A Field Emission Electron Microscope (FESEM) was used to evaluate the morphology of the composite and CNTs' bridging effect in the cement matrix. The results indicated the composite incorporating the 0.4 wt% Hybrid CNTs showed the highest increase in the energy absorption and improved the failure mechanism by decreasing the crack propagation and debris spatter.